2021
DOI: 10.3389/fchem.2021.660954
|View full text |Cite
|
Sign up to set email alerts
|

Protein Motifs for Proton Transfers That Build the Transmembrane Proton Gradient

Abstract: Biological membranes are barriers to polar molecules, so membrane embedded proteins control the transfers between cellular compartments. Protein controlled transport moves substrates and activates cellular signaling cascades. In addition, the electrochemical gradient across mitochondrial, bacterial and chloroplast membranes, is a key source of stored cellular energy. This is generated by electron, proton and ion transfers through proteins. The gradient is used to fuel ATP synthesis and to drive active transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 233 publications
(393 reference statements)
0
20
0
Order By: Relevance
“…Mutations of either Glu-L212, or Asp-L213, or Ser-L223 block proton transfer from the surface [228, 233, 234]. For further details, see [216, 225, 235237].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations of either Glu-L212, or Asp-L213, or Ser-L223 block proton transfer from the surface [228, 233, 234]. For further details, see [216, 225, 235237].…”
Section: Discussionmentioning
confidence: 99%
“…However, direct tracing of intra-protein displacements of protons in energy converting enzymes and chemical models (see [199,200,[207][208][209][210][211][212][213][214][215][216][217][218][219] for reviews) showed that fast proton transfer over a distance of up to 20 Å can be mediated by water bridges, provided that the distance between the groups involved is ≤ 3.0 Å, in accordance with Eigen [200]. Thereby it does not matter that water molecules are equally poor proton acceptors (with pKb of 0.0) and proton donors (with pKa of 14.0) because protons pass water by so-called von Grotthuss mechanism [220][221][222].…”
Section: Is Asp Wb An Universal Trap For a Proton From Wcat?mentioning
confidence: 99%
See 1 more Smart Citation
“…The ensemble of protein conformations broadens the distribution of protonation microstates since the residue proton affinity shifts as they sample different environments. Protonation states also change when ligands are bound , or when redox reactions occur at bound cofactors. , Proton pumps move protons through membrane embedded proteins as changes in protein conformation and redox states modify residue proton affinity. As with the protein conformational states, some protonation microstates are essential for protein function while others simply result from multiple microstates being close in energy.…”
Section: Introductionmentioning
confidence: 99%
“…Protonation states also change when ligands are bound 2,3 or when redox reactions occur at bound cofactors 7,8 . Proton pumps move protons through membrane embedded proteins as changes in protein conformation and redox states modify residue proton affinity [9][10][11][12][13] . As with the protein conformational states, some protonation microstates are essential for protein function while others simply result from multiple microstates being close in energy.…”
Section: Introductionmentioning
confidence: 99%